Mechanisms and Prevention of Open Globe Eye Injuries: Mehanizmi nastanka in preventiva odprtih poškodb očesa - Kuhta, Katja; Pahor, Dušica (Acta Medico-Biotechnica, 2021)
Purpose: Open globe injuries are a frequent cause of unilateral vision loss. The purpose of our study was to determine the epidemiological data of open globe injuries during a 15-year period in Central East Slovenia.Methods: A retrospective analysis of 219 patients (219 eyes) with open globe injuries admitted to the Department of Ophthalmology in the University Clinical Centre Maribor, Slovenia, from January 1999 to January 2014 was performed. We analyzed the following parameters: sex, age, month of injury, place of injury, type of injury, and mechanism of injury, grouped according to sex.Results: The majority of patients were male (186 patients, 85%). The mean age of male patients was 38 years with almost 45% of injuries occurring in the age interval between 30 and 50 years. Most injuries occurred during the colder part of the year from October to January. The most common place of injuries was the home (126 eyes, 66.5%). The most common open globe injuries were penetrating injuries (126 eyes, 57.6%) and rupture of the globe (49 eyes, 22.4%). Males most frequently experienced open globe injuries as a result of sharp objects (86 eyes, 46%), while in females, the most common causes of injuries were falls (10 eyes, 31%) and blunt objects (10 eyes, 31%).Conclusions: The vast majority of eye injuries are preventable. Studying the causes of injuries for a determined region is important to provide for preventable measures, like the use of eye protection, and to provide health education, to prevent severe vision loss or blindness.
Keywords: open globe injury; epidemiology; prevention; eye protection